2015
DOI: 10.1007/s11060-014-1704-y
|View full text |Cite
|
Sign up to set email alerts
|

Predicting early brain metastases based on clinicopathological factors and gene expression analysis in advanced HER2-positive breast cancer patients

Abstract: The overexpression or amplification of the human epidermal growth factor receptor 2 gene (HER2/neu) is associated with high risk of brain metastasis (BM). The identification of patients at highest immediate risk of BM could optimize screening and facilitate interventional trials. We performed gene expression analysis using complementary deoxyribonucleic acid-mediated annealing, selection, extension and ligation and real-time quantitative reverse transcription PCR (qRT-PCR) in primary tumor samples from two ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
211
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(211 citation statements)
references
References 37 publications
0
211
0
Order By: Relevance
“…The analysis of the correlation between BM patterns and previous systemic therapy showed that HER2-positive patients treated with trastuzumab before the diagnosis of BMs had a lower number of BMs in comparison with patients without HER2-targeted therapy. A protective role of the HER2-targeted therapy concerning the BMs was also suggested by the findings of Duchnowska et al, where no trastuzumab administration in the metastatic setting was an independent variable in the development of early BMs [8]. …”
Section: Discussionmentioning
confidence: 97%
“…The analysis of the correlation between BM patterns and previous systemic therapy showed that HER2-positive patients treated with trastuzumab before the diagnosis of BMs had a lower number of BMs in comparison with patients without HER2-targeted therapy. A protective role of the HER2-targeted therapy concerning the BMs was also suggested by the findings of Duchnowska et al, where no trastuzumab administration in the metastatic setting was an independent variable in the development of early BMs [8]. …”
Section: Discussionmentioning
confidence: 97%
“…The majority of the eligible studies were limited to reporting univariate association between BC subtypes or a single candidate factor with TTBM. Only fourteen studies provided multivariable TTBM estimates for variables [11,28,39,58,63,70,76,83,84,90,94,96,102,104].…”
Section: Group B -Prognostic Factors Associated With the Ttbmmentioning
confidence: 99%
“…With the exception of one study where only a small proportion of the patients received hormonotherapy or HER2 targeted therapies [106], studies that stratified patients into four BC subtypes (HR+/ HER2-, HR+/HER2+, HR-/HER2+ and HR-/HER2-) and measured TTBM interval from primary BC [28,38,54,86,90,92,97,100,104,105] or MBC diagnosis [28,38,55], the non-luminal subtypes (HR-/HER2-and HR-/ HER2+) were found to associate with significantly shorter TTBM, compared to the luminal ones (HR+/HER2-, HR+/HER2+). Comparison of the two HR-positive groups revealed HR/HER2 co-positivity to constantly associate with shorter TTBM [84,102]. Similar results were observed across seven studies [24,30,70,84,91,97,98] stratifying patients into three BC subtypes (HR+/HER2-, HR±/HER2+, and HR-/HER2-), with the TNBC tumors demonstrating the shortest TTBM (20-25.5 months from primary diagnosis and 9-14 months from MBC) and HR+/HER2-the longest (42-63.5 months from primary diagnosis and 20.6-34 months from MBC).…”
Section: Er Pr and Her2 Statuses And Ihc Bc Subtypesmentioning
confidence: 99%
“…The prognosis depends on multiple factors, such as stage and age at diagnosis, degree of differentiation, cellular proliferation, estrogen, and progesterone receptor positivity and overexpression of HER2/neu [2]. These factors also represent the basis of current therapies to HER2-targeted treatments or adjuvant/palliative hormonal treatment [3][4][5].…”
Section: Introductionmentioning
confidence: 99%